Йод і функціональна здатність щитоподібної залози у хворих на дифузний токсичний зоб - Пасєчко, Н. В.; Свистун, І. І. (Clinical Endocrinology and Endocrine Surgery, 2012)
As a result of determination of urinary iodine excretion in 36 patients with diffuse toxic goiter in iodine deficient region was marked decline of urinary iodine excretion that depends on severity of thyrotoxicosis at the beginning of disease. As a result of treatment by standard therapy (antithyroid drugs, beta-blockers) was defined with decreasing rates of hyperthyroidism urinary iodine excretion increased significantly. It can serve as the index of correct dose of antithyroid drugs.